2021
DOI: 10.3390/app11157167
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation Study of Flow and Heat Transfer in Swirling and Non-Swirling Impinging Jets on a Semi-Cylinder Concave Target

et al.

Abstract: Swirling impinging jet (SIJ) is considered as an effective means to achieve uniform cooling at high heat transfer rates, and the complex flow structure and its mechanism of enhancing heat transfer have attracted much attention in recent years. The large eddy simulation (LES) technique is employed to analyze the flow fields of swirling and non-swirling impinging jet emanating from a hole with four spiral and straight grooves, respectively, at a relatively high Reynolds number (Re) of 16,000 and a small jet spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It was observed from the results that heat transfer is enhanced more by well-separated multi-protrusions as compared to V grooves with close spacing. A numerical investigation was conducted by Xu et al [47] for studying the flow fields under jet impingement over a concave surface. The study was performed for swirling and non-swirling jets at a Reynolds number (based on the jet diameter) of 16,000 and jet-target surface spacing H/D = 2.…”
Section: Target Surface Shape and Spacing Between Jet Plate/nozzle And Target Surfacementioning
confidence: 99%
“…It was observed from the results that heat transfer is enhanced more by well-separated multi-protrusions as compared to V grooves with close spacing. A numerical investigation was conducted by Xu et al [47] for studying the flow fields under jet impingement over a concave surface. The study was performed for swirling and non-swirling jets at a Reynolds number (based on the jet diameter) of 16,000 and jet-target surface spacing H/D = 2.…”
Section: Target Surface Shape and Spacing Between Jet Plate/nozzle And Target Surfacementioning
confidence: 99%
“…In general, the studied swirling impinging jets had a greater spread rate and a more rapid decay in absolute velocity when compared to the non-swirling jet. Xu et al [17] used the LES method of swirling and non-swirling impinging jet from an orifice with four spiral and straight grooves. The local wall-adaptive turbulent viscosity model (WALEM) was chosen to study the relationship between the structure and the heat transfer properties of the square orifice and the spiral orifice for impinging jet cooling.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the shape of the target wall affects the stagnation area size and leads to the difference in flow characteristics of jet impingement cooling. Xu et al [19,20] studied and compared the heat transfer performance of swirling jet impingement cooling and circular hole jet impingement cooling on a semi-cylinder concave target by the large-eddy simulation method. They reported that the wall average Nusselt number of the 45 • angled swirling jet impingement cooling improves by 5% to 10% when compared with circular hole jet impingement cooling.…”
Section: Introductionmentioning
confidence: 99%